INSTITUTIONAL STRUCTURE OF THE SECURITIES MARKET AND ITS SIGNIFICANCE: THEORETICAL PERSPECTIVES - Nematullo ZUVAYDULLAEV, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This paper examines the institutional structure of the securities market and its significance in ensuring financial stability and market efficiency. It explores how regulatory bodies, legal frameworks, and financial intermediaries collectively influence transparency, investor protection, and market development. Using a qualitative and analytical approach, the study reviews theoretical perspectives from institutional economics and finance, highlighting that strong institutions reduce uncertainty and enhance investor confidence. The findings show that well-functioning institutional systems are essential for sustainable capital market growth, while weak structures hinder efficiency and trust. The paper concludes with recommendations for strengthening regulation, governance, and financial literacy to support resilient and transparent securities markets.